Pachuca Obsidian Blades from the U.S. Southwest: Implications for Mesoamerican Connections and Coronado's Mexican Indian Allies. Issue 4 (October 2021) - Dolan, Sean G.; Shackley, M. Steven
Abstract : The connection between people in the prehispanic U.S. Southwest / Northwest Mexico (SW/NW) and Mesoamerica is one of the most debated research topics in American archaeology. SW/NW groups used objects from Mesoamerica, but did they also trade for obsidian? Archaeologists have yet to find Mesoamerican obsidian from confirmed prehispanic SW/NW contexts, but here we discuss four green obsidian prismatic blades from New Mexico and Arizona. Using EDXRF spectrometry, we demonstrate that the blades are from the Pachuca source in Mesoamerica. The blades were found at four sites that the Spanish and their Mexican Indian allies used or potentially visited beginning in AD 1540. Using lithic technological organization and historical narratives, we assess the credibility of the different hypothesized models of prehispanic SW/NW-Mesoamerican interaction and obsidian use by the Mexican Indian allies. We suggest that green Pachuca blades would have been traded into the SW/NW if interaction with Mesoamerica had occurred more frequently. We also offer reasons why archaeologists have found so few Mesoamerican obsidian blades at post-1540 sites. This research is relevant because it expands our knowledge about SW/NW-Mesoamerican connections and the Mexican Indian allies of the Spanish, who are an underrepresented group in the archaeological and historical records.